Analysis mixed characterization of Kalimantan coal and mangrove wood charcoal character as briquette raw material. Issue 1 (November 2021) - Rahman, R; Azikin, B; Tahir, D; Widodo, S
Abstract: This study using three types of coal from East Kalimantan and South Sulawesi Mangrove Wood Charcoal which consisted of various compositions. In sample analysis using analysis, namely: proximate, ultimate, and calorific value. Proximate analysis: ash content, volatile matter, moisture content, fixed carbon; ultimate analysis: carbon and sulfur content and the calorific value using the bomb calorimeter method. The results of the proximate analysis showed that the fixed carbon content was obtained in the mixture of MWC 75% + KJA 25% = 52.45%, while the lowest was obtained at IC 100% = 32.86%; The highest volatile matter was obtained at KJA 100% = 44.23%, the lowest was at MWC 75% + KJA 25% = 31.90%, the highest ash content was IC 100% = 9.14% the lowest was at MWC 75% + KJA 25% = 5.94% and the highest moisture content was seen at IC 100% = 15.17% but MWC 75% + IC 25% = 9.52%. The results of the ultimate analysis showed that the lowest sulfur content was in the mixed variation of MWC 75% + KJA 25% = 0.168%, while the highest sulfur content was obtained at IC 100% = 0.874%. However, it was still in the low sulfur category <1. The highest calorific value is obtained by varying the composition at MWC 75% + IC 25% = 5919 cal/gram, while the lowest was obtained at KJA 100% = 4913 cal/gram. So based on this research, the addition of mangrove charcoal is very good for increasing the calorific value.